Penyebab dan Dampak Minim Keterbukaan Diri Remaja pada Orang Tua (Studi di Kp. Bangun Masjid Cadasari Pandeglang) - Silvia Tri Hastuti; Shelma Mauluddini; Devia Aprilianti; Najma Aghnia Nurizza; Siti Elut Kuraesin; Febri Anggun Viona; Hunainah (STKIP Subang, 2026)
This study aims to analyze the causes and impacts of low self-disclosure among adolescents toward their parents in Kampung Bangun Masjid, Cadasari District, Pandeglang Regency. The research used a descriptive qualitative method with adolescents aged 13–18 years as research subjects selected through purposive sampling. Data were collected through interviews, observations, and documentation techniques. The results showed that adolescents’ self- disclosure toward parents varied depending on family communication quality, parental responses, emotional comfort, and trust within the family. Adolescents who experienced warm and supportive relationships with parents tended to be more open in expressing feelings and personal problems. Meanwhile, adolescents who were afraid of being judged, scolded, or misunderstood preferred to keep their problems to themselves and share them with peers instead. The study also found that low self-disclosure had psychological impacts such as sadness, stress, confusion, and overthinking, as well as causing emotional distance between adolescents and parents. Therefore, open, empathetic, and supportive family communication is needed to create a safe space for adolescents to express their feelings and experiences.